Novel and Philosophy for Nikos Kazantzakis - Anayat, Abdelkrim; Al-Zuriqat, Zaid (Dirasat: Human and Social Sciences, 2022)
The research extrapolates the great interconnectedness between literature and philosophy of Nikos Kazantzakis. We cannot lose sight of the great connection between literature and philosophy at the moment of the emergence of philosophical thought in the Greeks from the so-called moment of establishment, and this relationship continued until the current crisis, and this is evident in the use of existential philosophy of the novel and play as a means of reporting abstract philosophical ideas. The research found that, the contemporary Greek writer Kazantzakis is considered one of the greatest novelists who have not been separated from philosophical problems. This is due to his philosophical formation by Bergson and Nietzsche. The question of the truth of man, and the question of the body that extended through the history of philosophical and religious thought together, added to this the issue of the symbolic value of art in the human being, which is inseparable from the divine and moral problem. We can also observe Kazantzakis’ involvement in postmodern discourse as a post-modern philosophy.